Strategy For Improving Education Quality Through The Managerial Function Of Madrasah Principals At Madrasah Tsanawiyah Nurul Haq Kasonan - Hayati, Rahmi; Dakir, Dakir (Journal Research of Social Science, Economics, and Management, 2025)
The quality of education is the main indicator in achieving national education goals, including in the madrasah environment. This article aims to analyze the managerial strategies of madrasah principals in carrying out managerial functions (planning, organizing, implementing, and supervising) to improve the quality of education at Madrasah Tsanawiyah Nurul Haq Kasongan, Central Kalimantan. This study uses a qualitative approach with data collection techniques through in-depth interviews and observations. The results of the study indicate that the madrasah principal carries out managerial functions in a participatory manner by involving all teachers in planning, dividing tasks according to individual capacity, and implementing programs through increasing curriculum understanding, teacher skills, and strengthening supervision. Supervision is carried out periodically by emphasizing learning evaluation and coaching-based follow-up. The committee and parents are also involved through partnerships built on trust and communication. The novelty of this article lies in the identification of value-based management practices that integrate spiritual, participatory, and adaptive approaches as a response to resource limitations. This approach shows that in the context of madrasas, the strength of collegial culture and institutional spirituality can be key factors in improving the quality of education in a sustainable manner.